Evaluation of fatigue behavior on repaired carbon fiber/epoxy composites - Botelho, Edson Cocchieri [UNESP]; Rezende, Mirabel C.; Mayer, Sergio; Voorwald, Herman Jacobus Cornelis [UNESP] (Springer, 2008)
The continuous use of structural polymer composites in aeronautical industry has required the development of repairing techniques of damages found in different types of laminates. The most usually adopted procedure to investigate the repair of composite laminates has been by repairing damages simulated in laminated composite specimens. This work shows the influence of structural repair technique on mechanical properties of a typical carbon fiber/epoxy laminate used in aerospace industry. When analyzed by tensile test, the laminates with and without repair present tensile strength values of 670 and 892 MPa, respectively, and tensile modulus of 53.0 and 67.2 GPa, respectively. By this result, it is possible to observe a decrease of the measured mechanical properties of the repaired composites. When submitted to fatigue test, it is observed that in loads higher than 250 MPa, this laminate presents a low life cycle (lower than 400,000 cycles). The fatigue performance of both laminates is comparable, but the non-repaired laminate presented higher tensile and fatigue resistance when compared with the repaired laminate.